Design of Surabaya T-Shirt Merchandise as a Medium for Promotion and Introduction of Historical Sites in the City of Surabaya - Muhammad Raffi Oxa Anandika Prasetyo; Irhamna Nirbhaya Carreca (Universitas Negeri Surabaya, 2026)
Surabaya is a major city in Indonesia that holds significant historical importance in the struggle for independence, particularly the events of November 10, 1945, which are commemorated as Heroes' Day. The stories, figures, and historical sites in Surabaya represent valuable heritage that needs to be introduced to the younger generation. However, young people’s interest in local history tends to decline because conventional historical presentation is often perceived as less engaging. At the same time, the younger generation is closely connected to visual culture and fashion as a means of self-expression. This study aims to design Surabaya historical-site-themed T-shirt merchandise as a communicative educational and promotional medium for young adults. Specifically, the study identifies representative historical sites in Surabaya, translates their historical and visual characteristics into T-shirt designs, develops supporting merchandise and digital media, and evaluates the design through stakeholder and target-audience feedback. Using the Design Thinking method, the study produced five T-shirt designs based on the Heroes Monument, Tunjungan Street, Hotel Majapahit, the Old Town, and the Red Bridge. The results show that minimalist architectural line-art, bold typography, limited historical color accents, short descriptions, coordinates, and QR-code-linked Instagram content can connect historical information with a contemporary fashion format. Stakeholder and user testing indicated that the designs were historically recognizable and visually relevant, although several technical revisions were needed in coordinate placement, front-back layout consistency, and line thickness. Therefore, Surabaya historical-themed T-shirt merchandise can function as an alternative medium for historical education, local identity promotion, and heritage-based creative products.